Pakistan : First Post-Program Monitoring Discussions-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses First Post-Program Monitoring Discussions with Pakistan. Pakistan's near-term outlook for economic growth is broadly favorable. Real GDP is expected to grow by 5.6 percent in FY2017/18, supported by improved power supply, investment related to the China-Pakistan Economic Corridor, strong consumption growth, and ongoing recovery in agriculture. Inflation has remained contained. However, continued erosion of macroeconomic resilience could put this outlook at risk. The FY2017/18 current account deficit could reach 4.8 percent of GDP, with gross international reserves further declining in a context of limited exchange rate flexibility.